THE ESSENTIAL STIMULATION IN CHILDREN OF THE MUNICIPAL SCHOOLS OF INFANTILE EDUCATION OF PANAMBI - RS (Fiep Bulletin - online, 2015)
The essential stimulation through stimulate of him existences it favors the child's best development in the aspect motor, cognitive, affective and social, looking for the potential maximum of your development.   This descriptive study, of traverse cut, with quali-quantitative analysis of the results and had as objective verifies how it happens the enrolled children's essential stimulation in EMEIs - Municipal Schools of Infantile Education of Panambi-RS. Participated of the study  children from 4 to 12 months of age that frequented the nursery of EMEis in the year of 2003, besides the directors and atendentes of the nursery.  It was used as evaluation instrument for direction and atendentes an interview semi - structured and for the children's evaluation neuropsicomotora the Card of the Child's Neurological Development was used, proposed by Coelho (1999). Observed that studied EMEIs possesses an atmosphere that favors the children's incentive there inserted and, so much the direction, as the atendentes know about the importance of taking place a work of essential stimulation as well as they are capable to notice some child it possesses some delay or difficulty in the development.  We believed that the actions of the school should be developed together with specialized professionals, in order to promote the health and the closest of the potential maximum of the children's development to arrive.
Keywords: Essential stimulation; Children; Infantile Education.